Silk fibroin micro-particle scaffolds with superior compression modulus and slow bioresorption for effective bone regeneration - Nisal, Anuya; Sayyad, Raeesa; Dhavale, Prachi; Khude, Bhakti; Deshpande, Rucha; Mapare, Vidhyashri; Shukla, Swati; Venugopalan, Premnath (Scientific Reports, 2018)
Silk fibroin (SF), a natural polymer produced by Bombyx mori silkworms, has been extensively explored to prepare porous scaffolds for tissue engineering applications. Here, we demonstrate, a scaffold made of SF, which exhibits compression modulus comparable to natural cancellous bone while retaining the appropriate porosities and interconnected pore architecture. The scaffolds also exhibit high resistance to in-vitro proteolytic degradation due to the dominant beta sheet conformation of the SF protein. Additionally, the scaffolds are prepared using a simple method of microparticle aggregation. We also demonstrate, for the first time, a method to prepare SF micro-particles using a Hexafluoroisopropanol-Methanol solvent-coagulant combination. SF microparticles obtained using this method are monodisperse, spherical, non-porous and extremely crystalline. These micro-particles have been further aggregated together to form a 3D scaffold. The aggregation is achieved by random packing of these microparticles and fusing them together using a dilute SF solution. Preliminary in-vitro cell culture and in-vivo implantation studies demonstrate that the scaffolds are biocompatible and they exhibit the appropriate early markers, making them promising candidates for bone regeneration.

Cold active lipases: biocatalytic tools for greener technology - Mhetras, Nutan; Mapare, Vidhyashri; Gokhale, Digambar (Applied Biochemistry and Biotechnology, 2021)
Lipases are enzymes that catalyze the ester bond hydrolysis in triglycerides with the release of fatty acids, mono- and diglycerides, and glycerol. The microbial lipases account for \$400 million market size in 2017 and it is expected to reach \$590 million by 2023. Many biotechnological processes are expedited at high temperatures and hence much research is dealt with thermostable enzymes. Cold active lipases are now gaining importance in the detergent, synthesis of chiral intermediates and frail/fragile compounds, and food and pharmaceutical industries. In addition, they consume less energy since they are active at low temperatures. These cold active lipases have not been commercially exploited so far compared to mesophilic and thermophilc lipases. Cold active lipases are distributed in microbes found at low temperatures. Only a few microbes were studied for the production of these enzymes. These cold-adapted enzymes show increased flexibility of their structures in response to freezing effect of the cold habitats. This review presents an update on cold-active lipases from microbial sources along with some structural features justifying high enzyme activity at low temperature. In addition, recent achievements on their use in various industries will also be discussed.
Keywords: Cold active lipases; Frail compounds; Psychrophilic microbes; Synthesis of chiral molecules